1987
DOI: 10.3109/03008208709006981
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Glycosaminoglycans in Human and Canine Menisci and their Attachments

Abstract: The semilunar meniscal body, horns and peripheral attachment were dissected from human and canine knee joints. The concentrations of hyaluronate, chondroitin sulfate, dermatan sulfate and keratan sulfate differed markedly among the tissues. The meniscal body was fibrocartilaginous but showed marked histological microheterogeneity with hyalinized areas intermixed with fibrous areas and contained mostly chondroitin sulfate and keratan sulfate. On the other hand, the fibrous peripheral attachment contained mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…described diffcrenccs in glycosaminoglycan concentrations between the two menisci (1). Interestingly, the data of Adams and Ho showed that, compared with the lateral meniscus, the medial meniscus contained higher concentrations of total glycosaminoglycan and more hyaluronate and chondroitin sulfate glycosaminoglycans but less dermatan sulfate chains (1). Our data demonstrated that, compared with the lateral meniscus, the medial meniscus contained significantly higher levels of mRNA for versican.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…described diffcrenccs in glycosaminoglycan concentrations between the two menisci (1). Interestingly, the data of Adams and Ho showed that, compared with the lateral meniscus, the medial meniscus contained higher concentrations of total glycosaminoglycan and more hyaluronate and chondroitin sulfate glycosaminoglycans but less dermatan sulfate chains (1). Our data demonstrated that, compared with the lateral meniscus, the medial meniscus contained significantly higher levels of mRNA for versican.…”
Section: Discussionsupporting
confidence: 48%
“…in their study on meniscal composition in human knees. described diffcrenccs in glycosaminoglycan concentrations between the two menisci (1). Interestingly, the data of Adams and Ho showed that, compared with the lateral meniscus, the medial meniscus contained higher concentrations of total glycosaminoglycan and more hyaluronate and chondroitin sulfate glycosaminoglycans but less dermatan sulfate chains (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations